BARD1 is an ATPase activating protein for OLA1 - Chen, Ting; Yeh, Hung-Wei; Chen, Po-Pang; Huang, Wei-Ting; Wu, Chu-Ya; Liao, Tzu-Chen; Lin, Shiou-Lan; Chen, Yi-Yun; Lin, Kai-Ti; Hsu, Shang-Te Danny; Cheng, Hui-Chun (Biochimica et biophysica acta. General subjects, 2022)
OLA1 is a P-loop ATPase, implicated in centrosome duplication through the interactions with tumor suppressors BRCA1 and BARD1. Disruption of the interaction of OLA1 with BARD1 results in centrosome amplification. However, the molecular interplay and mechanism of the OLA1-BARD1 complex remain elusive. Here, we use a battery of biophysical, biochemical, and structural analyses to elucidate the molecular basis of the OLA1-BARD1 interaction. Our structural and enzyme kinetics analyses show this nucleotide-dependent interaction enhances the ATPase activity of OLA1 by increasing the turnover number (kcat). Unlike canonical GTPase activating proteins that act directly on the catalytic G domain, the BARD1 BRCT domain binds to the OLA1 TGS domain via a highly conserved BUDR motif. A cancer related mutation V695L on BARD1 is known to associate with centrosome abnormality. The V695L mutation reduces the BARD1 BRCT-mediated activation of OLA1. Crystallographic snapshot of the BRCT V695L mutant at 1.88 Å reveals this mutation perturbs the OLA1 binding site, resulting in reduced interaction. Altogether, our findings suggest the BARD1 BRCT domain serves as an ATPase activating protein to control OLA1 allosterically. •BARD1 BRCT domain allosterically activates OLA1 ATPase.•The conserved BUDR motif in the BRCT interacts with OLA1.•Crystal structure reveals the molecular mechanism of disease mutation V695L in BARD1.